Knowledge, attitude, practices, and associated factors toward cervical cancer among female health sciences students of Addis Ababa University, Addis Ababa, Ethiopia - Sisay Endale; Kalkidan Delelegn; Zenebe Negash (Therapeutic Advances in Vaccines and Immunotherapy)
Background: Cervical cancer is the most common cancer in women worldwide. Early screening and vaccination can prevent cervical cancer; however, the low levels of knowledge, attitude, and practice among the young can contribute to the high prevalence of cervical cancer. Objective: This study aimed to assess the level of knowledge, attitude, and practice of cervical cancer and associated factors among female Health Sciences students of the College of Health Sciences at Addis Ababa University. Design: A descriptive cross-sectional study was conducted from February 2022 to June 2022 among regular undergraduate female Health Sciences students of Addis Ababa University. Methods: Data was collected using a self-administered questionnaire and analyzed using SPSS. Results were presented using descriptive statistics and bivariate analysis was conducted to look at the existence of significant associations and determine adjusted odds ratio. Statistical significance was declared at p -value ⩽0.05. Results: The majority of the study participants were within the age range of 18–24 years. From the 305 female Health Sciences students, almost all had heard about cervical cancer and 93.4% of them reported that human papillomavirus is the causative agent. About 75% of the respondents recognized at least one possible symptom of cervical cancer. Furthermore, nearly 70% and 78.3% of the participants showed positive attitudes toward taking and recommending human papillomavirus vaccines respectively. Only 16.1% and 48.9% of the respondents have good knowledge, and a positive attitude respectively. Surprisingly only 1.6% and 0.3% of the respondents have taken the human papillomavirus vaccine and undergone cervical screening respectively. Radiography technology students are about 86% less likely to have good knowledge compared to students in other fields of study ( p  = 0.04). Furthermore, year 4 and above students have significantly higher knowledge (89.2%) compared to those in years 1–3 (58%; AOR: 0.14, 95% CI: 0.05, 0.35). Conclusion: The knowledge of female Health Sciences students on cervical cancer was moderate, and about half had a positive attitude. However, their practice of human papillomavirus screening and vaccination was very low. Level of education and field of study were significantly associated with the knowledge of cervical cancer. Addressing gaps through awareness programs, and enhancing accessible health services can help empower these future health professionals.